2011
DOI: 10.1021/je200279q
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal Vapor–Liquid Equilibrium Data of Propan-1-ol + 2,2,4-Trimethylpentane and Butan-1-ol + 2,2,4-Trimethylpentane at 318.15 K

Abstract: In this research, vaporÀliquid equilibrium (VLE) data were determined at 318.15 K for the mixtures propan-1-ol + 2,2,4-trimethylpentane and butan-1-ol + 2,2,4-trimethylpentane in an isothermic Othmer still with recirculation, where the temperature was kept constant by means of a proportional-integral (PI) cascade control for the vapor phase. The equilibrium concentration for each phase was determined by gas chromatography, and the vapor phase was considered as nonideal. The consistency of the data was verified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…With these properties, ethanol-butanol mixture may be considered as promising oxygenated gasoline In order to design applicable oxygenated (nbutanol/ethanol) -gasoline blend, the knowledge of vapor pressure values for the systems containing ethanol, n-butanol and isooctane is necessary. Several studies have been reported for vapor pressure measurement of the binary systems containing isooctane, ethanol and n-butanol [10][11][12]. There was only one study reporting for vapor pressure of the ternary system containing isooctane, n-butanol and 1-hexene (without ethanol) [13].…”
Section: Introductionmentioning
confidence: 99%
“…With these properties, ethanol-butanol mixture may be considered as promising oxygenated gasoline In order to design applicable oxygenated (nbutanol/ethanol) -gasoline blend, the knowledge of vapor pressure values for the systems containing ethanol, n-butanol and isooctane is necessary. Several studies have been reported for vapor pressure measurement of the binary systems containing isooctane, ethanol and n-butanol [10][11][12]. There was only one study reporting for vapor pressure of the ternary system containing isooctane, n-butanol and 1-hexene (without ethanol) [13].…”
Section: Introductionmentioning
confidence: 99%